Analisis Pergeseran Makna dan Esensi dalam Pemberian Amplop pada Walimatul Urs di Desa Sokolelah Kadur Pamekasan - Kutsiyatur Rahmah (Fakultas Syariah IAIN Madura, 2024)
Giving money in an envelope during walimatul urs is a tradition practiced by the people of Sokolelah village. However, although giving envelopes has become a tradition, the majority of the people of Sokolelah village object to it, because for them the walimatul urs event is a form of gratitude for the bride and groom and should share with neighbors and relatives. With the giving of envelopes at the walimatul urs event, there is no difference between walimatul urs and what is called a reception. This research uses normative - empirical method withfield research. From the results of the research the author can conclude that the implementation of walimatul urs carried out by the people of Sokolelah village has experienced a shift in meaning and essence. While the review in Islamic law walimatul urs with the giving of envelopes is permissible because the giving of envelopes at the walimatul urs event can be said to be a gift or grant to the organizer of the event.